Jejak Peninggalan Kejuruan Selesai pada Masa Kesultanan Langkat - Sitorus, Faisal Nugraha; Irwansyah, Irwansyah; Faishal, Muhammad (Local History & Heritage, 2024)
This research discusses the traces of Kejuruan heritage scattered in the Langkat Sultanate area. In this context, the research aims to understand the background and significance of these relics, as well as finding answers to questions about how Kejuruan was maintained and used during the Sultanate of Langkat. The research method used is descriptive qualitative, with data collection through direct observation, interviews with local community leaders, and historical document analysis. The results revealed that Kejuruan had an important role in the life of the Langkat Sultanate community, especially in economic, social, and cultural contexts. This research also highlights the preservation efforts made to maintain the heritage of Kejuruan, as well as its implications in understanding local identity and history. Thus, this research makes a valuable contribution in enriching our understanding of the cultural heritage of the Sultanate of Langkat and the importance of its preservation for future generations.